Ethical religion in primary care. Issue 4 (4th July 2017) - Torry, Malcolm
Abstract: Religion is increasingly significant in UK society, and is highly significant for many patients and primary care practitioners. An important task for the practitioner is to ensure that the place of religion in the patient/practitioner relationship is treated with the same ethical seriousness as every other aspect of that relationship. The article finds the 'four principles of biomedical ethics' to be applicable, and recent GMC guidelines to be consistent with the four principles. The article applies the four principles to the particular case of practitioners wearing religious symbolism.